METHODS OF WORKING ON THE ARTISTIC PERFORMANCE OF THE WORK IN CHOIR TRAINING - Sh. A. Turdiyev (Journals Park Publishing, 2024)
This article provides information about working on the artistic performance of the work during musical training, performing choral works with emotion, revealing the artistic idea of the choral works during learning and singing, performing the work artistically as written by the composer.
Keywords: Choir performance, choral work, artistic performance, artistic polish, method of performance.